Penerapan Prinsip Restorative Justice pada Perkara KDRT di Tingkat Penyidikan Penyelidikan Kepolisian dan Tingkat Penuntutan Kejaksaan - Putri H. Yassin; Fence M. Wantu; Irlan Puluhulawa (PT PUSTAKA CENDEKIA GROUP, 2025)
This study was conducted to analyze the implementation of Restorative Justice (RJ) in handling Domestic Violence (DV) cases at the Bone Bolango Police Resort and the Bone Bolango District Attorney’s Office, with a focus on differences in considerations, procedures, and effectiveness. The research method employed a qualitative empirical approach through in-depth interviews with investigators and prosecutors, field observations, and analysis of legal documents. The results indicate that the Police tend not to apply RJ during the investigation stage due to regulatory limitations (Perpol No. 8/2021) and case complexity, whereas the Prosecutor’s Office is more flexible (based on Perja No. 15/2020), taking into account social impact and the principle of opportunity. RJ has proven effective for mild DV cases if the victim and perpetrator reach a peace agreement, but it requires strengthened regulations and victim protection. The study’s implications emphasize the importance of an ideal RJ model based on three principles: reparation of loss, perpetrator accountability, and community involvement, along with recommendations for officer training, establishment of community RJ Houses, and public outreach.